Integrasi Paham Agama: Membangun Kesamaan untuk Menegasikan Perbedaan Telaah Serat Sastra Gending - Riyadi, Muhammad Irfan (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2020)
Islamization in Mataram shows symptoms of transformation of the cultural system of society, from global to local culture, from great culture to little culture; Sultan Agung, the last student of Sunan Kalijaga, played an important role in this task. as the third king of the Mataram, he strongly criticized the Islamization model which did not build local conciusness because it uprooted the cultural roots of the community from where it had grown, which would hinder the process of Islamization and the process of community maturity. For this reason, he formulated his thoughts through allegorical poems in the Sastra Gending Literature text. The purpose of this study is to provide an interpretation of the literary Sastra gending so that an integrative acculturative pattern is found in concocting a phenomenal model of Islamization in the Mataram era. This study was carried out by exploring library data, which will be assembled by utilizing historical research methodology of thought, while analyzing the contents utilizing social hermeneutics. Conclusion This study has 2 things: 1) Serat Sastra Gending contains that’s about personal self-integration and divine integration; 2) According to Sultan Agung, human should understand the essence of religious teachings in a balanced way, it will make human life harmonious and peaceful, not mutually blaming and toppling each other. That is the point of preaching with the pacifique penetration model